(untitled) (Global Journal of Medical Research, 2022)
In the COVID-19 pandemic HRCT chest is often used by clinician to determine extent of their lung involvement The aim of this study is to assess the severity of lung involvement in confirmed suspected COVID-19 patients and its correlation to vaccination status with either COVISHIELD or COVAXIN in a tertiary care center This is a retrospective study in which our data is analyzed from 1st April 2021 to 30th April 2021 to identify patients 16 years who had confirmed positive RT-PCR or antigen test and received a HRCT Chest within 1st week Avg 3 5 days of RT-PCR Positive test to determine the extent of their lung involvement using the CT severity score CT-SS Patients were classified in 3 groups based on their vaccination status to determine its correlation with the CT-SS score fully vaccinated received 2 doses of vaccine partially vaccinated one dose of vaccine and unvaccinated Basic descriptive statistics Student t test and ANOVA test were done using Epi-info 7 1 software M S Windows